The role of Facebook in presenting gender perspectives in the Kurdistan Region - قادر, م.ى. سارا قادر; Ahmad, Asst.Prof.Dr.Araz Ramazan Ahmad (Sulaimani Journal for Humanities, 2025)
This study has worked to highlight the role of social media in presenting gender perspectives in the region Kurdistan, through an analysis of posts written about gender and analysis of his views People have spoken about this issue, how it has been reflected and how they have interpreted it in writing Or with pictures, cartoons or any other article they have contributed on this issue. The researcher relied on content analysis to analyze the posts and their contents through a detailed and intensive form Full of information to analyze the views of those who have commented on this issue on social networks Facebook has shown users that posts are received for a full year, the second six months of the year 2022 and the first six months of 2023, which was the heat of the debate on social media in particular Facebook social network. This research is based on the analytical method, and the method of analyzing the content of the posts in order to know the views and opinions of individuals, parties, groups, pages and accounts that are private They have written on gender issues and expressed their views. Also knowing the level of use Social media platforms and the role of those who have turned Facebook into a platform To change consumers' perceptions of gender in the Kurdistan Region, with its importance Social media users by posting gender issues. The researcher concluded his research with several conclusions Facebook users' attitudes to discussing gender issues were analyzed in the fifty posts. It turns out that the most users, to express their views Jindriyan have used fake pages and accounts It is not accepted in society, but everyone has interpreted it from the perspective and understanding they want Sometimes their analysis has misinterpreted the word and taken it in another direction The gender perspective in the posts is often characterized by defamation, ridicule and insult Most of them were published anonymously and without real pictures of the people. In general, text and pictures were used to express gender perspectives in the posts Their thoughts. Most of those who write about gender are male or identify themselves as male Females came in second place, but what needs to be addressed is the viewpoint Gender Posts rely less on sources and most are the opinion of the author.